Pelaksanaan Program Tahfidz Al-Qur’an: - Sholahuddin Ashani; Adli Walikhsan; Annisa Aurora; Arnita Suryani; Elda Ayumi; Hafis Sahputra; Imam Fahmi; Muhammad King Abdul Aziz (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2023)
This study aims to determine the implementation of the tahfidz al-Quran program at the Hifdzil Quran Madrasah Islamic Center Foundation North Sumatra and to find out the achievements of the mentoring program at the Hifdzil Quran Madrasah Islamic Center Foundation North Sumatra. This type of research is qualitative, the method used, namely the method of documentation and interviews. The population and sample of this study are: Santri, coaches, Head of the Hifdzil Quran Madrasah, and deputy director of the North Sumatra Islamic Center Foundation. The results of this study are: Implementation of the Al-Quran tahfidz mentoring program at the Hifdzil Quran Madrasah Islamic Center Foundation of North Sumatra, Program achievements tahfidz Madrasah Hifdzil Quran Islamic Center Foundation, namely, the 30 juz Tahfidz Al Quran Program was completed within 2 years, students also learned tahsin to continue to improve their Al Quran reading. Keywords: Al-Quran tahfidz program